2015
DOI: 10.1073/pnas.1422436112
|View full text |Cite
|
Sign up to set email alerts
|

Singlet fission in pentacene dimers

Abstract: Singlet fission (SF) has the potential to supersede the traditional solar energy conversion scheme by means of boosting the photonto-current conversion efficiencies beyond the 30% ShockleyQueisser limit. Here, we show unambiguous and compelling evidence for unprecedented intramolecular SF within regioisomeric pentacene dimers in room-temperature solutions, with observed triplet quantum yields reaching as high as 156 ± 5%. Whereas previous studies have shown that the collision of a photoexcited chromophore with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

58
647
1
19

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 409 publications
(731 citation statements)
references
References 38 publications
58
647
1
19
Order By: Relevance
“…[ 2,8 ] Interestingly, a recent study of pentacene dimers separated by a phenyl spacer unit achieved triplet yields above 100% in spite of using the same symmetric bonding motifs of the earlier tetracene dimers. [ 9 ] In this work, we report highly effi cient intramolecular SEF in a new type of covalent dimer, with triplet yields of up to 192 ± 3%. The molecule used in this study, 13,13′-bis(mesityl)-6,6′-dipentacenyl (DP-Mes, Figure 1 a), consists of two pentacenes directly bonded through a single C C bond with two bulky mesityl groups at the meso -positions.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…[ 2,8 ] Interestingly, a recent study of pentacene dimers separated by a phenyl spacer unit achieved triplet yields above 100% in spite of using the same symmetric bonding motifs of the earlier tetracene dimers. [ 9 ] In this work, we report highly effi cient intramolecular SEF in a new type of covalent dimer, with triplet yields of up to 192 ± 3%. The molecule used in this study, 13,13′-bis(mesityl)-6,6′-dipentacenyl (DP-Mes, Figure 1 a), consists of two pentacenes directly bonded through a single C C bond with two bulky mesityl groups at the meso -positions.…”
mentioning
confidence: 74%
“…By contrast, the recent study of pentacene dimers separated by a phenyl spacer showed a doubling of extinction coeffi cient upon dimerization. [ 9 ] Likewise, earlier studies of 9,9′-bianthryl, diphenylisobenzofuran dimers and tetracene dimers all reveal weakly coupled chromophores with extinction coeffi cients twice those (1) and reaction conditions for DP-Mes formation. b) DFToptimized (B3LYP/6-311G**) ground-state geometry of DP-Mes, demonstrating the orthogonality of the pentacenes (details in the Supporting Information).…”
Section: Energetic Structurementioning
confidence: 87%
“…Current investigations into the intermediates in singlet fission, e.g. bound triplet pair excimers 99 or strongly interacting triplet pairs, 136 etc., enabled by various monomer or dimer configurations 97,[137][138][139][140][141][142] will shed light on the dielectric environment needed to stabilize triplet excitons. Such interdisciplinary approaches will reveal the fundamental structure-property relationships affecting triplet diffusion in thin films, and ultimately enable the engineering of optoelectronic devices making use of multi-excitonic processes.…”
Section: Discussionmentioning
confidence: 99%
“…This means that the quantum yield ϕ ¼ N prod =N phot of the reaction, which describes the percentage of molecules that end up in the desired reaction product per absorbed photon, has a maximum value of 1. This limit can be overcome in some specific cases, such as in photochemically induced chain reactions [2-4], or in systems that support singlet fission to create multiple triplet excitons (and thus electron-hole pairs) in solar cells [5,6].Polaritonic chemistry, i.e., the potential to manipulate chemical structure and reactions through the formation of polaritons (hybrid light-matter states) was experimentally demonstrated in 2012 [7], and has become a topic of intense experimental and theoretical research in the past few years [8][9][10][11][12][13][14][15][16][17][18]. However, existing applications and proposals have been limited to enhancing or suppressing the rates of single-molecule reactions.…”
mentioning
confidence: 99%
“…This means that the quantum yield ϕ ¼ N prod =N phot of the reaction, which describes the percentage of molecules that end up in the desired reaction product per absorbed photon, has a maximum value of 1. This limit can be overcome in some specific cases, such as in photochemically induced chain reactions [2-4], or in systems that support singlet fission to create multiple triplet excitons (and thus electron-hole pairs) in solar cells [5,6].…”
mentioning
confidence: 99%